ANALISIS PENYERAPAN TENAGA KERJA PADA INDUSTRI KREATIF DI PROVINSI BALI - Diena Santi, Anak Agung Ratih; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
Labor absorption is an important issue in national and regional development. As one of the economic sectors in Bali Province, creative industry sector is expected to have high absorption rate to the workforce. This study aims to determine the effect of investment, wage levels and output values ??simultaneously and partially to the absorption of labor in creative industries in Bali Province. The data used in this study is secondary data obtained from Disperindag Province of Bali in the form of data period 2004 - 2017. The analysis technique used in this study is multiple linear regression analysis, by knowing the role of each independent variable influence on the variable bound. The result of the test with SPSS obtained the result that simultaneously the investment variable, wage rate and output value simultaneously have significant effect on the absorption of manpower in creative industry in Bali Province. Partially, the variable of wage rate and output value have positive and significant influence to the absorption of manpower in creative industry in Bali Province. While investment variables have a negative and significant effect on the absorption of labor in creative industries in Bali Province